Toxic potential of botulinum toxin type A on senescence in a Drosophila melanogaster model. (2021) - Fooladvand, Farnoosh; Tahouri, Vida; Baeeri, Maryam; Minaei, Tayebeh; Rahimifard, Mahban; Hodjat, Mahshid; Khorasani, Reza; Haghi-Aminjan, Hamed; Abdollahi, Mohammad
Graphical abstract: Highlights: Drosophila melanogaster can be used as a good model for investigating aging pathways. Botulinum toxin type-A induced dose-dependent cytotoxicity and oxidative stress in larvae of D. melanogaster . Botulinum toxin type-A induced DNA damage, activated caspase-3 and -9, and flies' body size reduction. Senescence markers, including β-galactosidase, p16, p21, p38, and p53, were down-regulated by Botulinum toxin type-A. Abstract: Botulinum toxin type-A (BoNT/A) application, especially neurological disorders, has been spread nowadays while it may cause side effects. The current study aimed to assess the BoNT/A dose-dependent effect on induction of aging in the Drosophila melanogaster model. The third instar larvae of Drosophila melanogaster were exposed to ¼ LC50, ½ LC50, and LC50 of BoNT/A in the Drosophila diet for 48 h while H2 O2 1% was used as a positive control. After the exposure time, some larvae were collected for molecular study, including gene expression analysis, comet assay, oxidative stress markers, and the phenotype changes. BoNT/A induced dose-dependent cytotoxicity, elevated reactive oxygen species (ROS) levels, and superoxide dismutase (SOD) enzyme activity. In addition, it caused DNA damage and activated caspase-3 and -9, and reduced the body size of the fly, especially in high doses. In line with the purpose of the study, aging markers, including β-galactosidase (β-gal), p16, p21, p38, and p53, were up-regulated by BoNT/A low dose. BoNT/A activates the aging pathway in the low dose, and increasing the dose induces toxicity, including oxidative stress, DNA damage, and apoptosis.